2020
DOI: 10.1371/journal.pone.0240682
|View full text |Cite
|
Sign up to set email alerts
|

An apparent-time study of an ongoing sound change in Seoul Korean: A prosodic account

Abstract: In present-day Seoul Korean, the primary phonetic feature for the lenis–aspirated stop distinction is shifting from VOT to F0. Some previous studies have considered this sound change to be a tonogenesis, whereby the low-level F0 perturbation has developed into tonal features (L for the lenis and H for the aspirated) in the segmental phonology. They, however, have examined the stop distinction only at a phrase- or utterance-initial position. We newly explore the sound change in relation to various prosodic stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…The focus effect of increasing F0 is consistent with Yun (2013) which found higher F0 for intervocalic lenis stops when phrases with the lenis stops in the phrase-medial positions were focused than when not focused. It has been also reported that F0 for both aspirated and lenis stops in word-and phrase-initial positions became higher with focus than without focus (Choi et al, 2020), demonstrating the similar focus effects on F0 between for the word-medial intervocalic stops and for the word-and phrase-initial stops.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The focus effect of increasing F0 is consistent with Yun (2013) which found higher F0 for intervocalic lenis stops when phrases with the lenis stops in the phrase-medial positions were focused than when not focused. It has been also reported that F0 for both aspirated and lenis stops in word-and phrase-initial positions became higher with focus than without focus (Choi et al, 2020), demonstrating the similar focus effects on F0 between for the word-medial intervocalic stops and for the word-and phrase-initial stops.…”
Section: Discussionmentioning
confidence: 66%
“…Kang & Guion (2008), for instance, showed that young speakers increased F0 for the wordand phrase-initial lenis and aspirated stops in clear speech (i.e., foreigner-directed speech) as compared to those in conversational speech. Choi et al (2020) also showed higher F0, as well as longer VOT, for the word-and phrase-initial lenis and aspirated stops when the stops were focused than when they were not. Note that in both studies, the aspirated and lenis stops differed in the degree to which their F0 and VOT values were manipulated by clear or focused speech, and as a result, for instance, the F0 distance between the stops became larger in clear and focused speech than in convertsational and unfocused speech, respectively.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Seoul Korean has been reported to show less difference in VOT between lenis and aspirated stops, but more f0 differences. It is also shown that the decrements of VOT difference and the enhancement of f0 difference were conditioned by the prominence of the syllables [ 22 ]. Specifically, they used a corrective focus task and examined disyllables.…”
Section: Introductionmentioning
confidence: 99%
“…This sound change is supported by the evidence of an increase in f0 differences and a reduction of VOT differences after lax and aspirated stops both from speech production [ 17 , 18 ] and perception studies [ 39 ]. [ 18 ] argued that the current sound change of Korean is at a stage of quasi-tonogenesis, in which the extra pitch feature is being phonologized and becoming distinctive over time [ 22 , 40 ]. The phonologization of the f0 differences is analyzed by some as phrase-initial prosodic strengthening [ 41 ] and a prosodically driven sound change [ 22 ].…”
Section: Introductionmentioning
confidence: 99%